Four new species of Physaraia (Hymenoptera: Braconidae: Braconinae) from Thailand - Chansri, Kittipum; Quicke, Donald L. J.; Butcher, Buntika A. (Zootaxa, 2022)
Four new species of the genus Physaraia Shenefelt, 1978 (Hymenoptera: Braconidae) from Thailand are described and illustrated based on female specimens collected from the Malaise traps and aerial net, increasing the total number of Physaraia species of Indo-Australian region to six species; P. nanensis Chansri, Quicke & Butcher, sp. nov., P. panhai Chansri, Quicke & Butcher, sp. nov., P. sakaeratensis Chansri, Quicke & Butcher, sp. nov., P. sinensis Quicke et al., 1997, P. sumatrana, Enderlein, 1905 and P. tigeri Chansri, Quicke & Butcher, sp. nov. A checklist to the species known of Physaraia with their distribution and dichotomous key to accommodate the new species are provided.